Effects of water-rock interaction on the dynamic mechanical properties and energy dissipation of pre-damaged granite - Zilong Wen; Huaibao Chu; Luyang Chen; Xiaolin Yang; Haixia Wei; Huazhe Jiao; Jinjin Yang; Fengbin Chen (PLoS ONE, 2025)
In deep rock mining, the surrounding rock is often simultaneously subjected to both an initial damage level induced by engineering disturbances and the effects of groundwater, and its stability is crucial for project safety. In this study, we take granite from a mine in Eastern China as the research object and conduct the Hopkinson test, electron microscope scanning test, X-ray diffraction (XRD) test, and elastic longitudinal wave velocity test under varying initial damage level and moisture content conditions. The main purpose of this study is to reveal the variation patterns of the dynamic mechanical properties and energy dissipation of granite specimens under the coupling effect of initial damage level and moisture content. The results show that the dynamic peak stress and peak modulus of granite specimens gradually decrease with increasing initial damage level and moisture content, reaching reductions of 41.6% and 60.6%, respectively, under an initial damage level of 28% and forced saturation. The water-damage weakening coefficient of the specimen increases as the initial damage level rises, making the water weakening effect more pronounced. At a constant initial damage level, the energy dissipation density of the specimen first increases and then decreases as the moisture content increases. As the initial damage level and moisture content increase, the fractal dimension of the specimen increases from 1.801 to 1.865, and the microscopic failure mode transitions from transgranular fracture to mixed-mode fracture, ultimately becoming dominated by intergranular fracture.The research results provide a reference for the stability evaluation and disaster prevention of deep rock mass engineering in water-rich conditions.